Challenges and strategies for collagen delivery for tissue regeneration - Lia Agustina; Andang Miatmoko; Dewi M. Hariyadi (AOSIS, 2023)
Background: Aged skin is characterized by wrinkles, hyperpigmentation, and roughness. Collagen is the most abundant protein in our body and it's responsible for skin health and it's mostly influenced by factors that accelerated aging such as UV. Objective: This study aimed to identify the potential use of collagen as skin supplementation and the challenges and strategies for its delivery. Methods: The articles were first searched through the existing database with the keyword of "collagen antiaging". The 585 articles were then screened by year of publication (2012-2022) resulted in 475 articles. The articles were then selected based on the delivery of collagen either orally or topically, resulted in 12 articles for further analysis. Results: Collagen has important roles in skin physiology by involving some mechanisms through inhibition of Mitogen-Activated Protein Kinase, induction of Tissue Growth Factor β (TGF-β), and inhibition of Nuclear Factor kappa beta (NF-κβ). The oral administration of collagen has an effective biological activity but requires large doses (up to 5 g daily). Meanwhile, the topical administration of collagen is limited by poor permeability due to high molecular weight (±300 kDa). Several strategies need to be carried out mainly by physical modification such as hydrolyzed collagen or entrapment of collagen using a suitable delivery system. Conclusions: Collagen could improve the skin properties, but further research should be conducted to increase its penetration either by physical modification or entrapment into suitable carrier.